'I Set My Foot Upon the Air and It Carried Me'. Issue 2 (3rd May 2016) - Mark, Elke
Abstract : Artistic research encourages us to let go of the handrail of known concepts and enter the field of a yet unfamiliar, dynamic, relational and sensuous knowledge. Performance art practice in particular offers alternative approaches which do not avoid the conflict with ideals that persistently strive for perfection and the assimilation of difference. It opposes a use-oriented reduction and instrumentalisation of sensuousness that leads to superficial and rudimentary modes of reception by 're-moving' an experience of the body in its resistance, its difference and its mysterious elusiveness, not least in order to win (back) the trust in its dignity and reliability. Starting by introducing and giving insight into processes within an Open Session, a work format which is practised, researched and continuously developed by the international performance art network and cross-disciplinary laboratory PAErsche, this paper emphasises concepts of performance art practice which challenge one's own attitude in order to investigate further in the field of encounter. Revisiting parameters of phenomenology, ethnomethodoloy and pedagogy, a self-confident performance art research practice is suggested to complement our conventional academic methods of knowledge production.